2021
DOI: 10.1186/s12879-021-06250-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Enterobacter cloacae complex in a tertiary Hospital in Northeast China, 2010–2019

Abstract: Background Carbapenem-resistant Enterobacter cloacae complex (CREC) is a new emerging threat to global public health. The objective of the study was to investigate the clinical characteristics and molecular epidemiology of CREC infections in the medical center of northeast China. Methods Twenty-nine patients were infected/colonized with CREC during a ten-year period (2010–2019) by WHONET analysis. Antibiotic susceptibilities were tested with VITEK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…Additionally, a majority of MCR-CREC belonged to epidemic clones, e.g. ST171, ST93, ST133, and ST418 [ 48 , 58 , 59 ], and the plasmids encoding MCR or carbapenemases were able to remain stable in ECC and self-transmissible as shown here. Despite that it remains unclear whether the resistance convergence in these epidemic clones has established evolutionary advantages, continuous surveillance is imperative to prevent them from being high-risk clones.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, a majority of MCR-CREC belonged to epidemic clones, e.g. ST171, ST93, ST133, and ST418 [ 48 , 58 , 59 ], and the plasmids encoding MCR or carbapenemases were able to remain stable in ECC and self-transmissible as shown here. Despite that it remains unclear whether the resistance convergence in these epidemic clones has established evolutionary advantages, continuous surveillance is imperative to prevent them from being high-risk clones.…”
Section: Discussionsupporting
confidence: 55%
“…It has been demonstrated that ECC is an opportunistic organism that can survive in a wide range of hosts, such as humans, animals, and plants. Molecular and biochemical analyses of the ECC have uncovered genomic and genotypic heterogeneity, and it now comprises the following Enterobacter species: E. cloacae , E. asburiae , E. hormaechei , E. kobei , E. ludwigii , E. mori , and E. nimipressuralis ( 2 ), of which E. cloacae and E. hormaechei are the most commonly discovered in clinical specimens from humans and animals, respectively ( 3 ). In addition, carbapenemase genes such as bla IMP , bla NDM , bla GIM , or bla KPC of plasmid origin have been identified in the ECC, not only creating the potential risk for transmission but also reducing the effectiveness of the carbapenems ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 As an opportunistic pathogen, ECC is ubiquitous not only in nature but also in clinical settings and has been associated with various infections, such as bacteremia, respiratory tract infections, wound infections, and urinary tract infections. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 As an opportunistic pathogen, ECC is ubiquitous not only in nature but also in clinical settings and has been associated with various infections, such as bacteremia, respiratory tract infections, wound infections, and urinary tract infections. 3,4 The prevalence of carbapenemase-resistant Enterobacteriaceae (CRE) has risen since the 2000s. 5 New Delhi Metalloβ-lactamase (NDM) is a type of Metallo-β-lactamase (MBL) able to hydrolyze most β-lactams (including carbapenems).…”
Section: Introductionmentioning
confidence: 99%